Analysis of working posture of coffee bean milling operators to reduce musculoskeletal disorder risks using the OWAS and REBA method - Mutia, Mutia; Iqbal, MT, Mohd; Hasanuddin, Iskandar (Politeknik Negeri Lhokseumawe, 2025)
Repetitive work involving lifting heavy loads over long distances and non-ergonomic working postures can lead to musculoskeletal disorders (MSDs). This problem is commonly found in coffee factories, particularly during the coffee bean grinding process, where two main activities are performed: the first is taking coffee beans from the ground, and the second is lifting the coffee beans to the grinding machine. The task of taking coffee beans from the ground involves a bent posture to collect them from a non-ergonomic coffee storage box. Meanwhile, in the task of lifting the beans to the grinding machine, workers must carry 25 kg of coffee over a distance of 8 meters. The purpose of this study was to evaluate work posture using the Ovako Working Posture Analysis System (OWAS) and Rapid Entire Body Assessment (REBA) methods. Six operators were observed at the coffee bean grinding station. The results show that three operators who perform the task of collecting beans from the ground received a category 3 score using the OWAS method, indicating that corrective action should be taken as soon as possible. In the task of lifting beans to the grinding machine, three operators received a score of 4 according to the OWAS method, also indicating that immediate corrective action is necessary. Based on the REBA method, three operators scored 10, classified as a high-risk level (action level 3), while the other three scored 11, indicating a very high-risk level. Based on these findings, it is necessary to provide ergonomic coffee storage boxes that accommodate workers’ posture in coffee factories and are easy to move according to the workers’ needs, to reduce the risk of musculoskeletal disorders.